Advent of a new civilization project: Eurasia in – U.S. out?. Issue 2 (July 2016) - Eremina, Natalia
International relations present the picture of integration and disintegration processes in vast territories stimulating different types of states' unions that have become the key points of international relations. Therefore the bulk of questions should be referred to the relationships between the states and the territory. This approach creates a geopolitical paradox revealing that the states' positions depend exactly on the territory and their geographical disposition, for instance, on distance from each other. So, the idea of shared territory and history allowed many European states to build up the European Union (EU). And now we are witnessing the same integration processes in the territory of ex-the USSR (Eurasian Economic Union), which is open for huge international actors like China, India and so on. It is of crucial importance to notify that these two international integration projects are in the territory of Eurasia. At the same time the majority of the EU member states are also connected with or even integrated into another international organization – NATO – with the United States (US) as the head and leader. It makes a clear division between the Atlantic macro-region and the Pacific macro-region underlying the role of the US in the contemporary international system. This role is unique but often hasty and irresponsible. Observation of the US's foreign politics through a geographical approach gives a perfect explanation of that. The US is simply geographically remote (despite the jet planes) from these two integration unions (from Eurasia) that allows them to feel the hegemon and influence the international processes there being at a distance. Therefore the main question nowadays is if the US can sustain their world leadership they have been claiming for, and that is what we aim to address in this article.